2013
DOI: 10.1089/jop.2012.0148
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Macular Hemorrhage Following Intravitreal Ranibizumab Injection for Neovascular Age-Related Macular Degeneration

Abstract: The systemic condition of subjects was found to be an important risk factor for newly developed or increased macular hemorrhage after IVR for neovascular AMD. More consideration should be given to the status of diabetes and hypertension in subjects who receive ranibizumab for neovascular AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In patients who were diagnosed as neovascular age-related macular degeneration (AMD), arterial hypertension was a strong risk factor for large subretinal hemorrhages,33 and antiplatelet or anticoagulant use was significantly associated with retinal or subretinal hemorrhage only in patients with hypertension 34. Previously, a significant association was reported between diabetes and hypertension with macular hemorrhage (including VH) after intravitreal injection for neovascular AMD 35. Consistently, our findings suggest the importance of cautious monitoring for VH risk in patients with AF on stroke prevention therapy with such clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who were diagnosed as neovascular age-related macular degeneration (AMD), arterial hypertension was a strong risk factor for large subretinal hemorrhages,33 and antiplatelet or anticoagulant use was significantly associated with retinal or subretinal hemorrhage only in patients with hypertension 34. Previously, a significant association was reported between diabetes and hypertension with macular hemorrhage (including VH) after intravitreal injection for neovascular AMD 35. Consistently, our findings suggest the importance of cautious monitoring for VH risk in patients with AF on stroke prevention therapy with such clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The systemic condition of subjects was found to be an important risk factor for newly developed or increased macular hemorrhage. 15 But according to our study even-though the presence of systemic diseases increases the severity of disease, its effect on psycho-social impairment is not significant.…”
Section: Discussionmentioning
confidence: 48%
“…16 In contrast, another study reported a rate of 8% for a new or increased subretinal hemorrhage in eyes with wet AMD being treated with ranibizumab. 17 MHs have been reported in conjunction with other conditions causing subretinal hemorrhages, such as retinal arterial microaneurysms (RAMs) 18,19 and trauma. 20 22 In the setting of trauma, it is unknown whether the MHs were typical traumatic MHs or whether the subretinal hemorrhage contributed to MH formation.…”
Section: Discussionmentioning
confidence: 99%